2021
DOI: 10.1016/j.ijcard.2020.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-Up of Patients with Heart Failure and Reduced Ejection Fraction Receiving Autonomic Regulation Therapy in the ANTHEM-HF Pilot Study

Abstract: Background:The ANTHEM-HF pilot study was an open-label study that evaluated the safety and feasibility of autonomic regulation therapy (ART) utilizing cervical vagus nerve stimulation (VNS) for patients with chronic HF with reduced EF (HFrEF). Patients in NYHA class II-III with EF ≤40% (n = 60) received ART for 6 months post-titration. ART was associated with sustained improvement in left ventricular (LV) function and HF symptoms at 6 and 12 months. Methods: Continuously cyclic VNS was maintained to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
0
22
0
1
Order By: Relevance
“…These preclinical and clinical advances considerably contributed to and streamlined the rapidly developing field of Bioelectronic Medicine ( Pavlov & Tracey, 2019a ). Bioelectronic VNS has now been explored in the treatment of numerous disorders and conditions including inflammatory and autoimmune diseases, pain, bleeding, heart failure, and the current opioid epidemic in the United States ( Czura et al, 2010 ; DiCarlo et al, 2018 ; Koopman et al, 2016 ; Pavlov & Tracey, 2019a ; Qureshi, Datta-Chaudhuri, Tracey, Pavlov, & Chen, 2020 ; Sharma et al, 2020 ). Implanted device-generated VNS, similar to VNS that is clinically-approved for the treatment of pharmacoresistant epilepsy and depression has been increasingly utilized and the underlying bioelectronic technology improved ( Levine, Faltys, & Chernoff, 2019 ).…”
Section: The Vagus Nerve and The Inflammatory Reflex: Mechanistic Insmentioning
confidence: 99%
“…These preclinical and clinical advances considerably contributed to and streamlined the rapidly developing field of Bioelectronic Medicine ( Pavlov & Tracey, 2019a ). Bioelectronic VNS has now been explored in the treatment of numerous disorders and conditions including inflammatory and autoimmune diseases, pain, bleeding, heart failure, and the current opioid epidemic in the United States ( Czura et al, 2010 ; DiCarlo et al, 2018 ; Koopman et al, 2016 ; Pavlov & Tracey, 2019a ; Qureshi, Datta-Chaudhuri, Tracey, Pavlov, & Chen, 2020 ; Sharma et al, 2020 ). Implanted device-generated VNS, similar to VNS that is clinically-approved for the treatment of pharmacoresistant epilepsy and depression has been increasingly utilized and the underlying bioelectronic technology improved ( Levine, Faltys, & Chernoff, 2019 ).…”
Section: The Vagus Nerve and The Inflammatory Reflex: Mechanistic Insmentioning
confidence: 99%
“…The Autonomic Neural Therapy to Enhance Myocardial Function in Heart Failure (ANTHEM-HF) evaluated the adjunct use of the Demipulse (LivaNova, Houston, TX) VNS system for left or right cervical vagal nerve stimulation in a cohort of patients with heart failure with reduced ejection fraction and New York Heart Association functional class II-III symptoms (Premchand et al, 2016;Dicarlo et al, 2018;Konstam et al, 2019;Sharma et al, 2020). Improvement in primary endpoints including left ventricular ejection fraction, heart rate variability, and 6-min walk tests, were noted, with follow-up at 1 year demonstrating persistent improvement (Figure 10; Premchand et al, 2016;Dicarlo et al, 2018;Konstam et al, 2019;Sharma et al, 2020). In the setting of heart failure with preserved ejection fraction (HFpEF), a more clinically challenging entity to treat, a similar VNS protocol by the same investigators is presently enrolling (Dicarlo et al, 2018).…”
Section: Vns For Treatment Of Cardiovascular Disease: Clinical Trialsmentioning
confidence: 99%
“…While pharmacologic therapy targets cardiac disease through neurohormonal blockade, results have not been as promising as hoped (Florea and Cohn, 2014;McMurray et al, 2014;. This has led to increasing interest in neuromodulation as a new therapeutic approach, with therapies such as vagal nerve stimulation (VNS) and video-assisted thoracoscopic sympathectomy showing efficacy for the treatment of heart failure and refractory ventricular arrhythmias (Schwartz et al, 2004(Schwartz et al, , 2008Wilde et al, 2008;Bourke et al, 2010;Vaseghi et al, 2014;Sharma et al, 2020). Though these early studies are promising, a better understanding of the anatomy and function of the cardiac nervous system is imperative to developing and implementing precise neuromodulatory therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, two large clinical trials failed to demonstrate that VNS could improve cardiac function or reduce mortality (10,11). Another study showed VNS was a promising therapy in heart failure (HF) (12)(13)(14)(15)(16). The interfaces and stimulation protocols used among the abovementioned studies were various, probably contributing to different results (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%